2015
DOI: 10.1038/ki.2014.427
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3β promotes cyst expansion in polycystic kidney disease

Abstract: Polycystic kidney diseases (PKDs) are inherited disorders characterized by the formation of fluid filled renal cysts. Elevated cAMP levels in PKDs stimulate progressive cyst enlargement involving cell proliferation and transepithelial fluid secretion often leading to end stage renal disease. The glycogen synthase kinase-3 (GSK3) family of protein kinases consists of GSK3α and GSK3β isoforms and plays a crucial role in multiple cellular signaling pathways. We previously found that GSK3β, a regulator of cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 72 publications
1
46
0
Order By: Relevance
“…The two isoforms of GSK3, GSK3α and GSK3β, have been recently shown to have distinct distributions in distal nephrons . In mouse kidney, both the α and the β isoforms were evidently expressed in mouse renal parenchyma, as shown by immunoperoxidase staining (Figure A).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The two isoforms of GSK3, GSK3α and GSK3β, have been recently shown to have distinct distributions in distal nephrons . In mouse kidney, both the α and the β isoforms were evidently expressed in mouse renal parenchyma, as shown by immunoperoxidase staining (Figure A).…”
Section: Resultsmentioning
confidence: 86%
“…This effect was dramatically attenuated in KO podocytes, suggesting a direct protective effect of GSK3β knockout on mitochondria injury. Dual colour staining for cleaved caspase-3 and mitochondria demonstrated that mitochondrial damage preceded overt apoptosis, and both were sequentially mitigated in KO podocytes upon ADR insult, inferring that the GSK3β mediates podocyte autonomous injury 33 lessened mitochondrial damage in KO podocytes is a primary effect of GSK3β ablation rather than an effect secondary to the anti-apoptotic action. Our latest data indicated that Cyp-F, a core structural constituent of the mitochondria permeability transition (MPT) pores, is a substrate for GSK3β [4].…”
Section: Gsk3β Knockout Mitigates the Adr-elicited Mitochondria Dysfumentioning
confidence: 95%
“…Ilk +/+ PKD kidneys showed a significant increase in ERK activity compared with WT. 55 Loss of one allele of ILK decreased P-ERK; however, this was NS. By contrast, ILK ablation in Ilk 2/2 PKD kidneys significantly reduced P-ERK.…”
Section: Effect Of Ilk On Cystic Diseasementioning
confidence: 90%
“…63 Fourth, pharmacological inhibition of glucogen synthase kinase 3 beta (GSK3beta), which accelerates cyst formation in cpk mice, leads to decreased Myc expression and amelioration of the cystic phenotype. 64 Similarly, Myc is down-regulated in Cys1 cpk/cpk ;Smad3 +/mice and such double mutants have a milder phenotype than cpk mice. 25 Our findings that complementation of mutant cpk with cystin-GFP rescues the cystic phenotype and restores normal Myc expression confirms that cystin acts in vivo as a negative regulator of Myc.…”
Section: Discussionmentioning
confidence: 99%